ANALYSIS OF LOW WALL SLOPE STABILITY AT PT ABC, A COAL MINE COMPANY - YUNI SARI PANE - Nim: 12114001 , MELYSA
Geotechnical engineering is defined as a study about slope stability. Geotechnical study has to be done when designing a mining acitivity to keep the workers safe. PT ABC is one of mining company in Indonesia that is located in East Kalimantan. PT ABC is actively mining and designing its mining activity with different toe-relativelevel for each year. Therefore, geotechincal study is needed to achieve safety factor greater than 1.3. The analysis is corred out in several low wall mining slope model based on mine design from PT ABC which created in the vertical cross section taken through the new geotechnic drill hole. Janbu method is applied for this analysis using Slide 6.0. version. The result shows that the whole low wall design is in unstable condition if saturation is assumed 100%, because safety factor is less than 1.3. The analysis then continued by lowering the heigh of low slope and decreasing the saturation. The result shows that lowering heigh of the slope is still not giving the significant result because safety factor is still less than 1.3. However, by lowering the saturation condition into 50%, it is found that the safety factor become greater than 1.3.